Varicella immunization requirements for US colleges: 2014–2015 academic year. Issue 6 (17th August 2016) - Leung, Jessica; Marin, Mona; Leino, Victor; Even, Susan; Bialek, Stephanie R.
ABSTRACT: Objective : To obtain information on varicella prematriculation requirements in US colleges for undergraduate students during the 2014–2015 academic year.Participants : Health care professionals and member schools of the American College Health Association (ACHA).Methods : An electronic survey was sent to ACHA members regarding school characteristics and whether schools had policies in place requiring that students show proof of 2 doses of varicella vaccination for school attendance.Results : Only 27% (101/370) of schools had a varicella prematriculation requirement for undergraduate students. Only 68% of schools always enforced this requirement. Private schools, 4-year schools, northeastern schools, those with <5, 000 students, and schools located in a state with a 2-dose varicella vaccine mandate were significantly more likely to have a varicella prematriculation requirement.Conclusions : A small proportion of US colleges have a varicella prematriculation requirement for varicella immunity. College vaccination requirements are an important tool for controlling varicella in these settings.